Community of practice in doctoral education - Mohd Tahir, Aida Hafitah; Asmuni, Azizan (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Communities of Practice (CoP) theory is important in understanding how adults learn, participate in practices, and create identity within the community or group. This paper explores on the relevance of CoP in the context of postgraduate study, specifically, in the field of doctoral education. The paper is aimed to analyse the use of CoP within different aspects of doctoral education and summarize the various forms of CoP within the learning environment of postgraduate education. A general review of some recent studies which had incorporated CoP within the doctoral education context was also included. The paper then elaborated on the concept of legitimate peripheral participation along with a discussion on CoP’s role towards developing academic identity among doctoral students. Finally, the future research on this topic was also discussed towards the end of the paper.